Spatial and temporal offsets between proxy records in a sediment drift - Ohkouchi, N.; Eglinton, T. I.; Keigwin, L. D.; Hayes, J. M. (Science, 2002)
Chronologies for Late Quaternary marine sediment records are usually based on radiocarbon ages of planktonic foraminifera. Signals carried by other sedimentary components measured in parallel can provide complementary paleoclimate information. A key premise is that microfossils and other indicators within a given sediment horizon are of equal age. We show here that haptophyte-derived alkenones isolated from Bermuda Rise drift sediments are up to 7000 years older than coexisting planktonic foraminifera. This temporal offset, which is apparently due to lateral transport of alkenones on fine-grained particles from the Nova Scotian margin, markedly influences molecular estimates of sea surface temperatures. More broadly, the observation raises questions about both the temporal and the geographic delity of paleoenvironmental records encoded by readily transported components of sediments.
612mqTimes Cited:147Cited References Count:38